2021
DOI: 10.1186/s12906-020-03145-6
|View full text |Cite
|
Sign up to set email alerts
|

Methodological flaws on “manual therapy for the pediatric population: a systematic review” by Prevost et al. (2019)

Abstract: Prevost et al. published a systematic review evaluating the use of manual therapy for clinical conditions in the pediatric population in 2019. However, several methodological flaws in the conduct of the review limit the internal validity of its conclusions. We caution readers about the validity of the recommendations and suggest that the review not be used to inform the clinical management of pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…We assessed the methodological risk of bias of the included studies using the Cochrane Collaboration’s risk-of-bias tool [ 10 ]. The overall risk of bias was assessed by the first author (PP) and validated by the other authors (BMK and AD), with disagreements settled through discussions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the methodological risk of bias of the included studies using the Cochrane Collaboration’s risk-of-bias tool [ 10 ]. The overall risk of bias was assessed by the first author (PP) and validated by the other authors (BMK and AD), with disagreements settled through discussions.…”
Section: Methodsmentioning
confidence: 99%
“…A review by Parnell Prevost et al (2019) suggested that inconclusive but favorable evidence does exist [ 7 ]. Subsequently, Yu et al 2021 [ 10 ] identified several methodological flaws in the conduct of this review, and a recent scoping review concluded that “no strong clinical recommendations can be made; and high-quality, scientifically rigorous research is required to evaluate safety, feasibility, and efficacy in pediatric populations” [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though there is a lack of evidence regarding the effectiveness of chiropractic care for pediatric patients [ 30 32 ], some studies have suggested that the emergence of adverse effects following manual therapy is rare in this population [ 27 29 ]. It has been well documented that parents consult chiropractors regarding their children, and it is the responsibility of members of the chiropractic profession to produce methodological and high-quality studies to investigate the effectiveness of care for the benefit of pediatric patients.…”
Section: Discussionmentioning
confidence: 99%